Journey to the Center of the Earth - Henry, Levin; Dahl, Arlene; Diane Baker; James Mason; Peter Ronson; Robert Adler; Thayer David; Pat Boone (USA Cooga Mooga, 1959)
Prof. Lindenbrook leads his intrepid party on an expedition to the centre of the earth, via a volcano in Iceland, encountering all manner of prehistoric monsters and life-threatening hazards on the way.
An Edinburgh professor and assorted colleagues follow an explorer's trail down an extinct Icelandic volcano to the earth's center.
Charles Brackett
Language(s): English Subtitle(s): No Subtitle
Keywords: Fantasy; SciFi; Adventure